Ciprofloxacin‐induced immune‐mediated thrombocytopenia: No cross‐reactivity with gemifloxacin. (8th August 2017) - Sim, D. W.; Yu, J. E.; Jeong, J.; Koh, Y.‐I.
Summary: What is known and objective: Fluoroquinolone‐induced immune‐mediated thrombocytopenia is uncommon, and no reports of cross‐reactivity among fluoroquinolones exist. Here, we describe a case of ciprofloxacin‐induced immune thrombocytopenia with no cross‐reactivity with gemifloxacin. Case description: A 77‐year‐old woman showed profound thrombocytopenia immediately after two ciprofloxacin injections for pneumonia. Platelet counts recovered rapidly after ciprofloxacin discontinuation. She had experienced thrombocytopenia after ciprofloxacin administration 4 years earlier, which was assumed to be ciprofloxacin‐induced immune‐related. Interestingly, no thrombocytopenia occurred following the subsequent exposure to another fluoroquinolone, gemifloxacin. What is new and conclusion: No cross‐reactivity occurred between ciprofloxacin and gemifloxacin in this fluoroquinolone‐induced immune thrombocytopenia case. Abstract : Changes in blood platelet count following administration of various antibiotics during admission.